New limits of tax law in the light of e-commerce taxation - E. Juchniewicz (Правоприменение)
The subject of the paper is the analysis of limits of taxation and tax law in the light of e-commerce taxationThe main aim of the paper is to show at the same time financial approach and philosophical approach to classic tax issuesThe methodology of the study includes general scientific methods (analysis, synthesis, description) as well as sociological approach.The main results and scope of their application. The use of new methodology in describing the limits of tax law is not only a matter of tax certainty but also a matter of future fiscal stability. All kinds of behaviours of the internet users we partially owe to the legal regulations. In this perspective, we can give many examples of implementation of the regulative function of law, including also tax law. Constant presence in the virtual world leads to the modification of the object of study. The commonly studied human impact in different areas of the virtual world, including also the creation of the law of Internet, is substituted with a new direction of studies - the analysis of the impact of the virtual world on the behaviour of its users. Not without significance to the issues of taxation of e-commerce are different models (simulations) of behaviours of objects of tax-law relations, which may constitute a basis, on the one hand - for the scientific studies, and on the other hand, the possibility to develop in due time appropriate institutions and mechanisms of tax law.The presence of new technologies that should be assessed in the light of limits of taxation. We must be aware of the fact that the modern day principles and techniques of taxation shall not stand the test of time and we will be forced to prepare ourselves for their radical change.Conclusions. Assuming that legal and financial relations are one of the main manifestations of statehood (sovereignty), and their content in terms of this study changes because of the occurring changes of technological nature, the changes in the existing legal and financial relations should be noticed, on the one hand, and on the other hand, the emergence of new legal and financial relations (e.g. legal and financial relation in cyberspace). Due to completely new legal and financial relations (possibly a new type of legal and financial relations), it must be assumed that the modern object of tax law is expanding. Logically, the object of financial law should be also scientifically extended in order to attempt to regulate the taxation in cyberspace or even taxation of robots (virtual robots).